ECOLOGICAL ASPECTS OF FORMATION OF MARKETING STRATEGIES FOR FURNITURE ENTERPRISES - Ivanusa , Andriy; Zagornyak , Vasyl (Forestry, Forest, Paper and Woodworking Industry, 2012)
Presented are the basic components of the marketing strategy of furniture enterprises in the context of ecological and economic characteristics of furniture manufacturing and furniture products. Analyzed were furniture products and ecological of aspects the main components of the marketing strategy of the furniture business: product, place, price, promotion, positioning.